China’s Development Journey: A Long-Trodden Path to Overcome the Great Divergence - Bhandari, Dadhiram (Apex Journal of Business and Management, 2024)
China’s largely sustained impressive economic resurgence of almost half a century has captivated the world; yet its journey to prosperity was marred by a prolonged divergence from Western Europe, known as the Great Divergence. This article analyzes the intricacies of this historical phenomenon, tracing the divergent paths of China and Western Europe from a shared starting point around the mid-eighteenth century. Drawing on a multidisciplinary approach, including historical analysis and economic theory, the paper tracks the underlying factors that propelled Western Europe ahead while China languished behind. It explores the role of environment, technology, and institutions in shaping the divergent trajectories of these economies. Additionally, this paper examines the enigma of China’s sustained economic growth amidst limited democratization, challenging conventional wisdom about the prerequisites of democracy for development. Through a cursory review of China’s modern development path, this paper sheds light on the intricate interplay of historical, institutional, and economic forces that have shaped China’s journey from early modern ear divergence to modern day resurgence.